2020
DOI: 10.1111/jcmm.15019
|View full text |Cite
|
Sign up to set email alerts
|

CircPRMT5 circular RNA promotes proliferation of colorectal cancer through sponging miR‐377 to induce E2F3 expression

Abstract: CircPRTM5 is associated with cell proliferation and migration in many kinds of malignancies. However, the functions and mechanisms of CircPRTM5 in CRC progression remain unclear. We explored the role and the mechanisms of CircPRTM5 in the development of CRC. Tissues of CRC patients and matched adjacent non‐tumour tissues were collected to evaluate the expression of CircPRTM5. The expression of CircPRTM5 in CRC tissues was significantly higher than that in adjacent tissues. The biological functions of CircPRTM5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…20 CircPRMT5 is also demonstrated to inhibit miR-30c and miR-377. 12,13 In our study, we also validated that miR-30c was sponged by circPRMT5. We demonstrated their direct interaction through luciferase reporter assay and RIP assay.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…20 CircPRMT5 is also demonstrated to inhibit miR-30c and miR-377. 12,13 In our study, we also validated that miR-30c was sponged by circPRMT5. We demonstrated their direct interaction through luciferase reporter assay and RIP assay.…”
Section: Discussionsupporting
confidence: 71%
“…17 CircPRMT5 was involved in bladder cancer and colon cancer. 12,13 However, whether circPRMT5 regulates PTC needs investigation. In this work, we found that circPRMT5 was upregulated in PTC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1b). Previous study has indicated that E2F3 was highly expressed and contributed to tumor progression in a variety of tumors, such as colorectal [19,20], melanoma [21][22][23][24][25] and bladder cancer [26][27][28][29]. We then (See figure on previous page.)…”
Section: Resultsmentioning
confidence: 93%
“…Both in vitro and in vivo experiments, Zhang demonstrated that high levels of miR-34a expression could inhibit the expression of direct target gene E2F3, and then inhibit the growth of CRC cells [29]. CircPRMT5 is an upstream regulator of E2F3 and it could promote the proliferation of CRC by inducing the expression of E2F3 [30]. Comparing with other E2F members, E2F4 has been reported in a lower extent.…”
Section: Discussionmentioning
confidence: 99%